Creatine in the fetal brain: A regional investigation of acute global hypoxia and creatine supplementation in a translational fetal sheep model - Tran, Nhi T.; Muccini, Anna M.; Hale, Nadia; Tolcos, Mary; Snow, Rod J.; Walker, David W.; Ellery, Stacey J. (Frontiers in Cellular Neuroscience, 2023)
Background: Creatine supplementation during pregnancy is a promising prophylactic treatment for perinatal hypoxic brain injury. Previously, in near-term sheep we have shown that fetal creatine supplementation reduces cerebral metabolic and oxidative stress induced by acute global hypoxia. This study investigated the effects of acute hypoxia with or without fetal creatine supplementation on neuropathology in multiple brain regions. Methods: Near-term fetal sheep were administered continuous intravenous infusion of either creatine (6 mg.kg−1.h−1) or isovolumetric saline from 122 to 134 days gestational age (dGA; term is approx. 145 dGA). At 131 dGA, global hypoxia was induced by a 10 min umbilical cord occlusion (UCO). Fetuses were then recovered for 72 h at which time (134 dGA) cerebral tissue was collected for either RT-qPCR or immunohistochemistry analyses. Results: UCO resulted in mild injury to the cortical grey matter, thalamus and hippocampus, with increased cell death and astrogliosis and down-regulation of genes involved in regulating injury responses, vasculature development and mitochondrial integrity. Creatine supplementation reduced astrogliosis within the corpus callosum but did not ameliorate any other gene expression or histopathological changes induced by hypoxia. Of importance, effects of creatine supplementation on gene expression irrespective of hypoxia, including increased expression of anti-apoptotic (BCL-2) and pro-inflammatory (e.g., MPO, TNFa, IL-6, IL-1β) genes, particularly in the grey matter, hippocampus, and striatum were identified. Creatine treatment also effected oligodendrocyte maturation and myelination in white matter regions. Conclusions: While supplementation did not rescue mild neuropathology caused by UCO, creatine did result in gene expression changes that may influence in utero cerebral development.